Formação de mesoporos na síntese de zeólitas ZSM-5 via nanomoldagem avaliação no craqueamento de n-decano - Silva, Camila Ramos da (2008)
The use of zeolites in the cracking of hydrocarbons is limited because the molecules higher than 0.74 nm do not diffuse in their micropores. In the other hand, molecular sieves as MCM-41, MCM-48 ou SBA-15, whose diameters are up 10 nm for the two formers and up to 30 nm for the last, have low hydrothermal stability and catalytic activity. To overcome those limitations, many studies are devoted to prepare materials, which can combine the high activity of zeolites with the better accessibility of the mesoporous materials. Among the possible methods, the synthesis of zeolites in confined spaces (nanocasting) it is seem as a powerful alternative. In this method: 1) a mesoporous or non-porous silica is impregnated with an organic compound, which act as a carbon precursor, after being carbonized; 2) the porous carbon is subsequently obtained by treatment with hydrofluoric acid or alkaline hydroxides; 3) the porous of the carbon are filled with the zeolite synthesis gel, which is formed after crystallization; 4) finally, the mold of the carbon and the template of the zeolite microstructure are eliminated by calcination. In the present work, it was used the above described method for the synthesis of nanocasting ZSM-5 zeolites using porous carbon, which were prepared from non-porous or mesoporous silica moulds (MCM-41, MCM-48 e SBA-15). The XRD of the prepared zeolites did not show diffraction peaks in the low angle region (< 5°2θ), showing that the inverse replica of the mesoporous silicas was not obtained. However, the nitrogen sorption measurements evidenced the presence of mesoporous, which resulted from the carbon nanotubes occluded during the ZSM-5 crystals formation. The mesopores observed in the Znp, nanocast from non-porous silica, were attributed to the inter-crystalline spaces generated by the agglomeration of ZSM-5 nanocrystals. The mesoporous formation in the ZSM-5 zeolites during the crystallization in a confined space (nanocating) was considerately favored by the ageing of the synthesis gel at the laboratory temperature and without stirring. That procedure allows the preparation at 180 °C of ZSM-5 zeolites with high crystallinity and in a lower time. Nevertheless, as verified by 27Al-NMR, the aluminum was incorporated partially in the zeolite microstructure, remaining as alumina in the crystal surface, which leads to a lower activity in the n-decane cracking when compared with a conventional ZSM-5 zeolite with a similar Si/Al ratio.